Vigilância eletrônica no direito processual penal: uma reflexão a partir de Michel Foucault - Menezes, Aldo Botana (2010)
From Michel Foucault and Gilles Deleuze ideas, this research analyzes the electronic individuals monitoring. People sentenced precisely under the law of criminal procedure. The electronic surveillance suggests a natural philosophical interest that revolves around the analysis of issues relating to power, prison, law, the society of discipline and control. Foucault critical texts about power are the guiding track of this research, in order that it allows investigating the procedures related to electronic surveillance that focus on the conduct of individuals sentenced by the State. The analysis of this subject relates to the modern prison management activity, whose way of criminal sanction counts on a significant transformation: the enforcement of criminal punishment can be effective even in distance, that is, outside the prison environment. From this philosophical pathway we recognize that the electronic surveillance is a form of exercise of disciplinary power, where the effects of their relationship fall onto the body of each condemned and extends beyond the prison population. The existence of a society of control suggests that disciplinary mechanisms are expanded in order that we can find an unfinished constitution of the new society, this new social overview that values the progress of technology